PERLINDUNGAN HUKUM ANAK PIDANA DALAM PERSPEKTIF MAQASID ASY-SYARI’AH (Studi Kasus Penanganan Anak Pidana di Lembaga Pemasyarakatan Jambi) - Marsaid, Marsaid (Nurani, 2015)
Abstract: Indonesia as a country with social cultured law, dueto the influence of globalization shows the behavior of thepeople in his life increasingly complex. Such behavior can beseen from two sides, namely in accordance with the norms andnot in accordance with the norm, so that such conditions spreadto the entire line of people's lives. This article will exploreproblems criminal children who are in prison in Jambi.ملخص: اندونیسیا كدولة للقانون مثقف الاجتماعي ، ویرجع ذلك إلى تأثیر العولمة یدلعلى سلوك الناس في حیاتھ یزداد تعقیدا . ویمكن رؤیة مثل ھذا السلوك من الجانبین ،وھي وفقا ل معاییر ولیس وفقا ل معیار بحیث یمكن لھذه الظروف انتشرت في خطكامل من حیاة الناس. ھذه المادة سوف استكشاف مشاكل الأطفال الجنائي الذین ھم فيالسجن في جامبيKata Kunci: Anak Bermasalah dengan Hukum (ABH)